Anti‐Diabetic Activity of Flavonol Glucosides From Fumana montana Pomel: In vitro Analysis, In Silico Docking, ADMET Prediction, and Molecular Dynamics Simulations. Issue 8 (20th February 2023) - Laraoui, Habiba; Lanez, Elhafnaoui; Zegheb, Nadjiba; Adaika, Aicha; Lanez, Touhami; Benkhaled, Mohammed
Abstract: One of the major challenges in type 2 diabetes is the inhibition of the enzyme alpha‐amylase, since many molecules targeting this enzyme based on or derived from medicinal plants have been synthesized to counteract the α‐amylase action. The present study investigated the in‐vitro and in‐silico antidiabetic capacities of three flavonol glucosides obtained from the plant Fumana montana Pomel using α‐amylase inhibition model. α‐amylase binding interaction with the studied compounds was examined using ultraviolet‐visible absorption spectroscopy technique. Molecular docking and ADMET prediction were also performed for the three phytoconstituents towards human pancreatic alpha‐amylase receptor. The in vitro results revealed that both compound FG1 and FG3 showed a higher antidiabetic activity (84.00±0.12 and 85.36±0.12 μg/ml respectively) than that of standard antidiabetic acarbose (91.12±0.11). The value of the binding free energy ranging from −31.66±0.07 to −32.68±0.03 KJ mol −1 demonstrated the spontaneity and the strong binding betweenα‐amylase and the studied phytoconstituents. Molecular docking study indicated the preferred binding site and binding mode, and further suggested that the binding mode of the three compounds to the target enzyme is of hydrogen bonding and hydrophobic forces. Further analysis by molecular dynamic simulation studies showed that FG2 was stable in the HPA active site. In vitro and in‐silico results showed that the studied phytoconstituents interacted with α‐amylase and their binding interaction resulted in reduction of the enzyme's activity. Abstract : The work describes the anti‐diabetic activity of 3 flavonol glucosides extracts from Fumana montana Pomel using spectroscopic assays and molecular docking investigations. The anti‐diabetic activity was measured against the alpha‐amylase. The molecular docking study was carried out to measure the inhibition activity and binding parameters of the phytoconstituents compounds with the enzyme alpha amylase. The best pose from the docking used for the molecular dynamic simulation in order to confirm the stability of the ligand.